KONSEP DIRI ANAK PEKERJA SEKS KOMERSIAL YANG TINGGAL DITENGAH MASYARAKAT - Fatchun Nikmah (Journal of Research and Measurement in Psychology, 2017)
Abstract Stigma in today's society considers more sex workers as the dregs of society who only regarded as an immoral person who violates the norms of religion and society, so they are not appreciated. A prostitute is almost the majority have families, both parents, brother, husband or child. Communities usually negative view sex workers family and those views may influence the psychological development of child prostitutes. This study aims to determine the child's self-concept of prostitutes who live in the community.This study uses a qualitative case study approach, which is a special phenomenon that is present in a limited context, although the boundaries between phenomenon and context are not entirely clear. Determination techniques are the subject of the researchers used snowball sampling or chain sampling. The research was conducted in two villages that are within the scope of the district in one district on the island of Java. The subject of this study were children and adolescents aged prostitute who is still undergoing formal schooling.This study found that the first subject has a good self concept. There is not much of a gap between the basic self-concept and ideal self-concept on the subject. The first subject has a perceptual self-concept is not good because the subject is not satisfied with the current physical condition and there are gaps in the basic perceptual components and ideal self-concept. As for the conceptual and attitudinal self concept self concept can be considered a good subject because there is no gap between the conceptual and attitudinal components of the basic categories and ideal self-concept. While the second subject has a poor self-concept, as there are many gaps between the basic self-concept and ideal self concept on the subject. The subject has a perceptual selfconcept is not good, because the subject was not satisfied with his physical condition and his subjects make the situation as a benchmark of the ideal situation for him. In addition, the subject has attitudinal poor self concept. Keywords: Self-concept, children, sex workers, society, qualitative